Revisiting the Effect of FDI and Trade Openness on Carbon Dioxide in Indonesia: Modelling the Environmental Kuznets Curve - Effendi, Rustam; Aliasuddin, Aliasuddin; Samsudin, Hazman; Rahmi, Nanda; Fachrurrozi, Kamal (International Journal of Energy Economics and Policy, 2024)
This research reexamines the relationship between foreign direct investment (FDI) and trade openness (TO) on carbon emissions in Indonesia by using the Environmental Kuznets Curve (EKC) approach. Thus, economic growth and urbanization variables are introduced in the study to depict the level of sustainable development in Indonesia. The study was conducted by utilizing the Autoregressive Distributed Lag (ARDL) approach, covering the period from 1990 to 2020. The primary findings reveal that FDI positively impacts carbon emissions both in the short and long term. On the other hand, trade openness is found to have a positive influence only in the long term, with no effect in the short term. Economic growth, which is reflected by the Environmental Kuznets Curve (EKC), exhibits a U-shaped pattern, while urbanization significantly influences carbon emissions in both the short and long term. This shows that economic development in Indonesia is somewhat bend away from sustainable development. Based on these results, it is recommended that FDI and trade openness is directed towards promoting better technology which are environmental friendly. Furthermore, promoting the consumption of green goods is essential for fostering a sustainable development, and efforts should be made to reduce the rate of urbanization.